Indications, challenges, and characteristics of successful implementation of perioperative registries in low resource settings: A systematic review - Belachew, Fitsum Kifle (Division of General Surgery, 2023)
Background Data is central to healthcare system improvement. Perioperative registries can be utilised for quality improvement initiatives through tracking outcomes, developing risk prediction models, and supporting policymakers and health professionals in making evidence-based decisions and interventions. This is particularly desirable in low-resource settings, where there is an unmet surgical demand and patients have a mortality rate up to double that of high-income countries. To better understand and support initiatives to establish clinical registries, this study aimed to assess the indications, challenges, and characteristics of successful perioperative registries in low-resource settings from the available literature on perioperative registry implementations. Materials and Methods We conducted a librarian-assisted literature search of international research databases; PubMed, Scopus, Cochrane Library, Web of Science, and WHOLIS WHO Library Database of articles published between January 1969 to January 2021 using controlled subject headings and keywords. Studies were filtered using predefined criteria and responses to two Mixed Method Appraisal Tool screening questions. A Direct Content Analysis Method was used to synthesize data for eligible studies based on predefined criteria. Results The search identified 2793 abstracts, with ten studies included after removing duplicates and excluding studies that did not meet eligibility criteria. Three were conducted in South America, four in Africa, two in the Middle East, and one in Asia. The lack of context-specific data for determining and evaluating patient outcomes (n=7) was the major indication for implementing registries. Organizing local research teams and engaging stakeholders in the host country was associated with successful implementation. However, inadequate funding to hire data collectors and monitor data quality was identified as a major challenge (n=4). Conclusion The goal of a perioperative registry is to generate data to influence and support quality improvement, and national surgical policies. Efforts to establish perioperative registries must continue while adhering to local ethical practices and broader principles and should consider those characteristics associated with successful registry implementation identified in this review.